Mobile unemployment in a post-industrial society: The case of Sweden - Mats Johansson; Lars Olof Persson (European Regional Science Association (ERSA), 1998)
Since the early 90s, every region in Sweden has been struck by high unemployment, especially among young persons. In the same period, there has been an overrepresentation of unemployed among inter-regional migrants. Increasingly, however, this mobility does not lead to employment. Yet, there are largely economic factors explaining this mobility. There seems to be a dual spatial pattern of this phenomenon. Preferably, unemployed migrate to (a) metropolitan regions and to (b) rural areas. This indicates that the phenomenon is multifaceted. Mobile unemployed have different backgrounds and different aspirations. Unemployed migrants to rural areas are predominantly low cost seekers who do not look for a regular job any longer. Unemployed migrants to metropolitan regions are to a large extent recent immigrants and/or young persons attracted by the informal segments of the urban labor market. The aim of the paper is to describe emerging patterns of inter-regional migration of unemployed, to analyze the socio-economic careers of different migrant groups, and to analyze factors leading to mobile unemployment. The factors analyzed include changes in the welfare system and in labor market policy. Finally, the paper will discuss the regional economic consequences of the emerging pattern and the policy implications.
Keywords: 330